Application of Phenoclimatographic Models in Stone Fruits Protecting from Spring Frosts - Odyntsova, Valentyna; Sushko, Serhii; Сушко, Сергій Леонідович; Сушко, Сергей Леонидович; Bondarenko, Larysa; Бондаренко, Лариса Юріївна; Бондаренко, Лариса Юрьевна; Scherbakova, Nina; Щербакова, Ніна Володимирівна; Щербакова, Нина Владимировна (Springer International Publishing, 2019)
EN: The study of the stages of morphogenesis in generative buds along with the quantitative accumulation of GDH made it possible to establish the influence of the interaction of two extreme environmental factors on the growth and development of the buds. The factors (minimum and maximum air temperatures) were considered as parameters for phenoclimatographic models. These indicators determined the elements of irrigation control. The control signal was transmitted to the actuators of the irrigation system. Incoming and outgoing information registration was provided. A functional and structural diagram of the irrigation system control unit has been developed. The positive experience of using of fine-dispersed sprinkler for evaporative cooling of the buds on the trees with the aim of delaying their development was outlined. That provided the indirect method of protecting plantings from spring frosts.
Keywords: Phenoclimatographic models; Irrigation; Protecting plantings; Buds; Digital indicator; GDH accumulation